GEFs and Rac GTPases control directional specificity of neurite extension along the anterior–posterior axis - Zheng, Chaogu (Proc Natl Acad Sci U S A, 2016)
Although previous studies have identified many extracellular guidance molecules and intracellular signaling proteins that regulate axonal outgrowth and extension, most were conducted in the context of unidirectional neurite growth, in which the guidance cues either attract or repel growth cones. Very few studies addressed how intracellular signaling molecules differentially specify bidirectional outgrowth. Here, using the bipolar PLM neurons in Caenorhabditis elegans, we show that the guanine nucleotide exchange factors (GEFs) UNC-73/Trio and TIAM-1 promote anterior and posterior neurite extension, respectively. The Rac subfamily GTPases act downstream of the GEFs; CED-10/Rac1 is activated by TIAM-1, whereas CED-10 and MIG-2/RhoG act redundantly downstream of UNC-73. Moreover, these two pathways antagonize each other and thus regulate the directional bias of neuritogenesis. Our study suggests that directional specificity of neurite extension is conferred through the intracellular activation of distinct GEFs and Rac GTPases.